Arquitectura del desengaño: fragmentación del sujeto en Espejo de gran niebla de Guillermo Carnero (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
This contribution carries out a reading of Guillermo Carnero’s Espejo de gran niebla (2002) focusing on those metapoetic aspects that reveal the fallacies in the representations of the lyrical subject. This collection of poems presents a journey through the poet’s memory, triggered by the experience of falling out of love, which is transferred to a renewed questioning of the modalities of fictional representation. The point of innovation of this collection of poems, with respect to the previous ones, is a radical and explicit distrust towards the supposed self-narrative modalities, the fall of previous the culturalist masks, as well as a new openness towards sentimental expression.
Keywords: Guillermo Carnero; "Espejo de gran niebla"; metapoetry; lyrical subject.